2017
DOI: 10.17951/pjss.2016.49.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Sheep and Horse Grazing in a Large-Scale Protection Area and its Positive Impact on Chemical and Biological Soil Properties

Abstract: Abstract. This paper looks into the impact of free grazing by sheep and horses on the chemical and biological properties of soils in the partial protection zone of the Roztocze National Park. The study sampled three different types of pastureland in the area: pastures for sheep, horses and for combined grazing by sheep and horses. Compared to an ungrazed reference pasture, free grazing significantly stimulated the activity of enzymes which catalyze the transformation of organic matter (dehydrogenases, phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…humus usually takes the form of a calcimorphic mull or calcimorphic mull-moder (mocek and Drzymała 2010). Futa et al (2016) demonstrated changes in the chemical properties of soils under the effects of extensive farm animal grazing after 3-4 years of grazing.…”
Section: Dcmmentioning
confidence: 99%
See 1 more Smart Citation
“…humus usually takes the form of a calcimorphic mull or calcimorphic mull-moder (mocek and Drzymała 2010). Futa et al (2016) demonstrated changes in the chemical properties of soils under the effects of extensive farm animal grazing after 3-4 years of grazing.…”
Section: Dcmmentioning
confidence: 99%
“…the introduction of extensive sheep grazing to habitats to provide major biodiversity growth, such as the grassland habitats of the eastern territory of lublin region (kąty Plh060010, stawska Góra Plh060018, zachodniowołyńska Dolina bugu Plh060035) covered by the biostratEG project (biostratEG2/297267/14/nCbr/2016), can improve their protection and the lasting use of biological and landscape diversity. the return to extensive grazing of farm animals enables the optimising of both commercial and protective actions (Futa et al 2016). it is, therefore, a form of sustainable protection for grassland habitats in natura 2000 areas.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the value of both pastures shows that the fertile pasture contained more plants of good or very good value, while the poor pasture featured more species of sufficient or low value. The abundance of macro-elements and the enzymatic activity of the soil are the factors observed in this case (Futa et al, 2016). Sand calcareous grasslands usually feature species of low value and of low aboveground biomass yield (Benthien et al 2018;Dostálek and Frantík, 2008;Kulik et al, 2013;Süss et al 2004;Warda et al 2011).…”
Section: Biomass Valuementioning
confidence: 94%
“…That is why, whenever possible, it is recommended to alternate the grazing of sheep or cattle with other animals, which increases the utilisation of the sward and reduces the likelihood of infection with intestinal parasites (Pilliner, 2008). Shared grazing also influences the biological and structural development of the soil (Futa et al 2016). Roztocze National Park is one of the areas where various native livestock breeds are grazed in order to protect permanent grasslands against secondary succession.…”
Section: Journal Of Ecological Engineeringmentioning
confidence: 99%
“…Azken urteetan, ekidoek ingurumenean duten eragin positiboa frogatzen duten ikerketa zientifiko asko garatu dira. Alde batetik, jakina da zaldien bazkatze estentsiboak paisaia heterogeneoa mantentzen duela (Fleurance et al, 2016), eta biodibertsitatea eta lurraren kalitatea hobetzen dituela (Futa et al, 2017;Ringmark et al, 2019). Ekidoek otea (errekorra den landare zurkara) jaten dute kalitatezko belarrik eskuragarri ez dutenean, eta horrekin batera, baso-suteak prebenitzen laguntzen dute (Rigueiro-Rodríguez et al, 2012).…”
Section: Sarrera Eta Motibazioaunclassified